The Impact of Chronic Severe Preoperative Local Infection on Postoperative Complications and Recurrence Following Winograd Procedure for Ingrown Toenail of the Great Toes: A Retrospective Cohort Study - Ji Yong Yun; Jin Soo Suh; Yun Beom Lee; Jun Young Choi (Journal of Clinical Medicine, 2026)
Background/Objectives: The Winograd procedure is a widely utilized surgical option for treating ingrown toenails. However, there is a lack of comparative data regarding its outcomes in the presence of active infection. The objective of this study was to compare the clinical outcomes and complication rates of the Winograd procedure for great toe ingrown toenails between patients with and without chronic severe preoperative local infection. Methods: This retrospective study included 388 great toes that underwent the Winograd procedure for ingrown toenails between 2015 and 2025 with minimum 6 months’ follow-up. Cases were categorized into two groups based on the presence (Group 1, n = 76) or absence (Group 2, n = 312) of preoperative signs of severe local infection (abscess, granulation tissue formation, and/or foul odor). Demographic factors, and clinical outcomes, including postoperative infection rates, antibiotic duration, and recurrence rates, were evaluated and compared between the two groups. Results: Patients in Group 1 were significantly younger (29.7 vs. 39.5 years; p = 0.001) and had a higher smoking prevalence (11.8% vs. 5.1%; p = 0.033) than those in Group 2. Postoperatively, the mean duration of antibiotic administration (13.9 vs. 10.6 days; p = 0.114) and the incidence of superficial operative site infection (31.6% vs. 28.2%; p = 0.561) showed no significant differences between the two groups. Persistent infection lasting more than three weeks was comparable (15.8% vs. 11.5%; p = 0.313), with similar antibiotic durations in these cases (33.0 vs. 36.6 days; p = 0.094). Most importantly, the postoperative recurrence rate did not differ significantly between the two groups, with 13.2% in Group 1 compared to 15.3% in Group 2 (p = 0.625). Conclusions: Immediate Winograd procedure with radical excision of infected granulation tissue showed no statistically significant differences in postoperative complication or recurrence rates, even in patients with chronic severe preoperative local infection. These findings suggest that immediate surgical intervention can be considered a feasible treatment option for direct source removal.